Analysis of the results of pedagogical experiment on development of culture-creating competence in teachers-humanitarians of military higher educational institutions of Ukraine - Zamotaieva, Nataliia (ScienceRise: Pedagogical Education, 2017)
The article analyzes the course and results of experimental-research check of effectiveness of elaborated theoretical model of development of culture-creating competence of teachers-humanitarians of MHEI in the system of post-graduate pedagogical education. The theoretical model of development of culture-creating competence of military higher school teachers was grounded and elaborated using case-technology. The psychological-pedagogical conditions of development of culture-creating competence of MHEI teachers-humanitarians were determined. The logic, organizational features and course of pedagogical experiment at each its stage were elucidated, the results of experimental-research teaching were generalized. The conclusions of the study were made; the prospects of further study of considered scientific question were indicated. It was established, that culture-creating competence of MHEI teachers-humanitarians is manifested in their readiness for productive pedagogical activity, subject-subject interaction with pupils on the base of acquired totality of culturological knowledge, skills, esthetic experience, humanistic ideals and values, creative abilities and talent of co-creative activity that is remarkable for dynamic character and need permanent deepening, widening, renewal, practical training. Introduction of the author’s model of culture-creating competence development of MHEI teachers-humanitarians using case-technology allows essentially optimize post-graduate training (re-training), qualification improvement of teachers of military higher school. The prospects for further elaboration of considered scientific question that are in substantiation and projecting of new case typology, creation of case “battery” on topical pedagogical problems, study of the ways of integration of case-technology with interactive technologies of cooperated, communicative-dialogue, playing study were determined